67‐3: Invited Paper: Progress in Electronic Paper Displays: Color Video Electrofluidic Display Technology. Issue 1 (28th June 2021) - Sun, Hailing; Tang, Biao; Jiang, Hongwei; Groenewold, Jan; Henzen, Alex; Zhou, Guofu
Abstract : Electronic paper displays have been well known as many superb features but currently find a limited application space in dedicated reading devices and shelf labels, the next generation electronic paper displays are highly expected the breakthrough in full color and video speed. In this perspective, we give an overview on the recent progress on color video electro‐fluidic display technology, in particular recent developments in modeling, materials, manufacturing, driving and industrialization.